Data Citation and Availability: Striking a Balance Between the Ideal and the Practical. Issue 11 (5th November 2016) - Hapgood, Mike; Knipp, Delores J.
Abstract: This editorial explores some of the challenges that arise when the space weather community seeks to implement AGU data policy. It shows that many important space weather data sets are hard to cite to modern standards and encourages community discussion on how best to strike a balance between the ideals of that data policy and its practical implementation.